8-(2-Cycloalkylphenylimino)-5, 6, 7-trihydro-quinolylnickel halides: polymerizing ethylene to highly branched and lower molecular weight polyethylenes1. Issue 3 (3rd March 2015) - Sun, Zelin; Yue, Erlin; Qu, Mengnan; Oleynik, Irina V.; Oleynik, Ivan I.; Li, Kanshe; Liang, Tongling; Zhang, Wenjuan; Sun, Wen-Hua
<x xml:space="preserve">Abstract</x> Cycloalkyl-modified 8-arylimino-5, 6, 7-trihydroquinolylnickel pre-catalysts highly polymerize ethylene into branched polyethylene waxes.